Analysis of Material Variations (Ammonium Perchlorate / Aluminum / Epoxy) And Pressure on Propellant Combustion Speed - Hidayat, Teguh Rakhmat; Whidiyanto, Purwo; Maryono, Maryono; Mangililo, Richard Costantin; Zai, Andy Saputra (Evrimata: Journal of Mechanical Engineering, 2024)
In this research, a comparative analysis of propellant combustion speed was carried out with variations in AP/Al/Epoxy materials and pressure variations. The higher the pressure, the greater the speed of combustion. Based on the results of the research, the relationship between the air pressure provided is directly proportional to the combustion speed and the mass flow rate of the propellant. The greater the pressure applied, the higher the combustion speed and propellant mass flow rate. The best performance is found in propellant B with a value of n = 0.44. A constant value close to 0 (zero) indicates a much more sensitive level of propellant sensitivity. The resulting mass flow rate at an initial atmospheric pressure of 0.332 gr/s and at an initial pressure of 5 bar is 0.791 gr/s